360°-multiple object tracking in team sport athletes: Reliability and relationship to visuospatial cognitive functions. (July 2021) - Ehmann, Paul; Beavan, Adam; Spielmann, Jan; Ruf, Ludwig; Mayer, Jan; Rohrmann, Sonja; Nuß, Christian; Englert, Chris
Abstract: Introduction: In team sports, the ability to visually track the movements of teammates and opponents simultaneously is a critical aspect of success. In sports psychology, this ability can be examined with the help of the multiple object tracking paradigm . The current study investigated the relationship between task performance in a novel 360°-multiple object tracking task and visuospatial cognitive functions as well as the reliability of the task. Methods: In a sample of 153 team sport athletes the relationships between performance in the 360°-multiple object tracking task and performance in a spatial attention task, a spatial working memory task, and a fluid intelligence task at a first time of measurement were investigated . Additionally, at a second time of measurement the test-retest reliability of the 360°-multiple object tracking task was measured over a six-week interval in a subsample of 65 athletes. Results: The expected significant correlations between the performance in the 360°-multiple object tracking task and the tasks measuring spatial attention and working memory were observed. Test-retest reliability analysis indicated a good reliability of the procedure. Conclusions: The results of this study demonstrate that the novel 360°-multiple object tracking task allows the reliable assessment of visuospatial cognitive performance of athletes in a dynamic 360°-environment . Highlights: 360°-version of the multiple object tracking task improves task representativeness. Performance in the task is related to spatial attention and working memory. 360°-tracking task is reliable procedure to assess cognitive functions of athletes.